Keeping Safe and Providing Support: A Participatory Survey About Abuse and People With Intellectual Disabilities. Issue 3 (10th September 2013) - Northway, Ruth; Bennett, Davey; Melsome, Mel; Flood, Samantha; Howarth, Joyce; Jones, Richard
Abstract: People with intellectual disabilities are at increased risk of abuse, but their views regarding this have not been explored. The authors undertook a study in Wales to examine what help people with intellectual disabilities feel they need to keep safe and, if they are abused, what support they need. A questionnaire was distributed to 47 participants with intellectual disabilities attending a residential research event and as a postal survey across Wales. From this, 107 (56%) usable questionnaires were returned. Respondents identified most strategies for keeping safe as being useful but were more likely to identify personal strategies rather than actions other people could take. When abuse does occur, having a trusted person to speak to and one who will believe you were viewed as the most important aspects. The authors noted that people with intellectual disabilities can identify personal safety strategies and their views and experiences should inform personal safety courses and staff training. Furthermore, they recommend that effective circles of support need to be developed both to protect against abuse and to provide support should it occur.